f ( x ) d x = \frac { x ^ { 3 } } { 3 } - \frac { x ^ { 2 } } { 2 } - 2 x
Solve for d (complex solution)
\left\{\begin{matrix}d=-\frac{12+3x-2x^{2}}{6fx}\text{, }&x\neq 0\text{ and }f\neq 0\\d\in \mathrm{C}\text{, }&x=0\text{ or }\left(x=\frac{3-\sqrt{105}}{4}\text{ and }f=0\right)\text{ or }\left(x=\frac{\sqrt{105}+3}{4}\text{ and }f=0\right)\end{matrix}\right.
Solve for f (complex solution)
\left\{\begin{matrix}f=-\frac{12+3x-2x^{2}}{6dx}\text{, }&x\neq 0\text{ and }d\neq 0\\f\in \mathrm{C}\text{, }&x=0\text{ or }\left(x=\frac{3-\sqrt{105}}{4}\text{ and }d=0\right)\text{ or }\left(x=\frac{\sqrt{105}+3}{4}\text{ and }d=0\right)\end{matrix}\right.
Solve for d
\left\{\begin{matrix}d=-\frac{12+3x-2x^{2}}{6fx}\text{, }&x\neq 0\text{ and }f\neq 0\\d\in \mathrm{R}\text{, }&x=0\text{ or }\left(x=\frac{3-\sqrt{105}}{4}\text{ and }f=0\right)\text{ or }\left(x=\frac{\sqrt{105}+3}{4}\text{ and }f=0\right)\end{matrix}\right.
Solve for f
\left\{\begin{matrix}f=-\frac{12+3x-2x^{2}}{6dx}\text{, }&x\neq 0\text{ and }d\neq 0\\f\in \mathrm{R}\text{, }&x=0\text{ or }\left(x=\frac{3-\sqrt{105}}{4}\text{ and }d=0\right)\text{ or }\left(x=\frac{\sqrt{105}+3}{4}\text{ and }d=0\right)\end{matrix}\right.
Graph
Share
Copied to clipboard
6fxdx=2x^{3}-3x^{2}-12x
Multiply both sides of the equation by 6, the least common multiple of 3,2.
6fx^{2}d=2x^{3}-3x^{2}-12x
Multiply x and x to get x^{2}.
\frac{6fx^{2}d}{6fx^{2}}=\frac{x\left(2x^{2}-3x-12\right)}{6fx^{2}}
Divide both sides by 6fx^{2}.
d=\frac{x\left(2x^{2}-3x-12\right)}{6fx^{2}}
Dividing by 6fx^{2} undoes the multiplication by 6fx^{2}.
d=\frac{2x^{2}-3x-12}{6fx}
Divide x\left(2x^{2}-3x-12\right) by 6fx^{2}.
6fxdx=2x^{3}-3x^{2}-12x
Multiply both sides of the equation by 6, the least common multiple of 3,2.
6fx^{2}d=2x^{3}-3x^{2}-12x
Multiply x and x to get x^{2}.
6dx^{2}f=2x^{3}-3x^{2}-12x
The equation is in standard form.
\frac{6dx^{2}f}{6dx^{2}}=\frac{x\left(2x^{2}-3x-12\right)}{6dx^{2}}
Divide both sides by 6x^{2}d.
f=\frac{x\left(2x^{2}-3x-12\right)}{6dx^{2}}
Dividing by 6x^{2}d undoes the multiplication by 6x^{2}d.
f=\frac{2x^{2}-3x-12}{6dx}
Divide x\left(2x^{2}-3x-12\right) by 6x^{2}d.
6fxdx=2x^{3}-3x^{2}-12x
Multiply both sides of the equation by 6, the least common multiple of 3,2.
6fx^{2}d=2x^{3}-3x^{2}-12x
Multiply x and x to get x^{2}.
\frac{6fx^{2}d}{6fx^{2}}=\frac{x\left(2x^{2}-3x-12\right)}{6fx^{2}}
Divide both sides by 6fx^{2}.
d=\frac{x\left(2x^{2}-3x-12\right)}{6fx^{2}}
Dividing by 6fx^{2} undoes the multiplication by 6fx^{2}.
d=\frac{2x^{2}-3x-12}{6fx}
Divide x\left(2x^{2}-3x-12\right) by 6fx^{2}.
6fxdx=2x^{3}-3x^{2}-12x
Multiply both sides of the equation by 6, the least common multiple of 3,2.
6fx^{2}d=2x^{3}-3x^{2}-12x
Multiply x and x to get x^{2}.
6dx^{2}f=2x^{3}-3x^{2}-12x
The equation is in standard form.
\frac{6dx^{2}f}{6dx^{2}}=\frac{x\left(2x^{2}-3x-12\right)}{6dx^{2}}
Divide both sides by 6x^{2}d.
f=\frac{x\left(2x^{2}-3x-12\right)}{6dx^{2}}
Dividing by 6x^{2}d undoes the multiplication by 6x^{2}d.
f=\frac{2x^{2}-3x-12}{6dx}
Divide x\left(2x^{2}-3x-12\right) by 6x^{2}d.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}